1969
DOI: 10.1086/267724
|View full text |Cite
|
Sign up to set email alerts
|

Interviewing a National Sample by Long-Distance Telephone

Abstract: Changing emphases in programs of social welfare, including public health, make it increasingly necessary to plan and conduct programs responsive to the subjective needs and values of the consumer groups for whom they are intended. Obtaining information about such needs in turn requires the development of inexpensive but valid tools for collecting data.In recent years the telephone has seen increasing use as a means of collecting data quickly and inexpensively. Despite some limitations, a small number of publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…After examining return rates from 1952 through 1979, Steeh (1981) concluded that refusal rates were rising. For example, Kegeles, Fink, and Kirscht (1969) reported a refusal rate of 4% for participation in their James Jones is affiliated with Ball State University.…”
Section: Introductionmentioning
confidence: 99%
“…After examining return rates from 1952 through 1979, Steeh (1981) concluded that refusal rates were rising. For example, Kegeles, Fink, and Kirscht (1969) reported a refusal rate of 4% for participation in their James Jones is affiliated with Ball State University.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, those shortcomings of the telephone survey are avoided. In fact, some reinterviews of samples of the entire age range by telephone have obtained high response rates (e.g., Kegeles, Fink, and Kirscht, 1969;Rogers, 1976), and a recent resurvey of an older sample has obtained a 76% response rate if only respondents were included for the response rate calculation, a 93% response rate if respondents and proxies were included (Kovar and Fitti, 1985).…”
mentioning
confidence: 99%
“…When supplemental contacts were made, the response rate tends to reach the same fairly high level regardless of the method used to make the contacts (Coombs & Freedman, 1964;Herman, 1977;Hochstim, 1967;Kegeles, Fink, & Kirscht, 1969;Rogers, 1976;Schmiedeskamp, 1962;Siemiatycki, 1979).…”
Section: Mode Of Communicationmentioning
confidence: 98%